If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + 8)(w + -3) = 0 Reorder the terms: (8 + w)(w + -3) = 0 Reorder the terms: (8 + w)(-3 + w) = 0 Multiply (8 + w) * (-3 + w) (8(-3 + w) + w(-3 + w)) = 0 ((-3 * 8 + w * 8) + w(-3 + w)) = 0 ((-24 + 8w) + w(-3 + w)) = 0 (-24 + 8w + (-3 * w + w * w)) = 0 (-24 + 8w + (-3w + w2)) = 0 Combine like terms: 8w + -3w = 5w (-24 + 5w + w2) = 0 Solving -24 + 5w + w2 = 0 Solving for variable 'w'. Factor a trinomial. (-8 + -1w)(3 + -1w) = 0Subproblem 1
Set the factor '(-8 + -1w)' equal to zero and attempt to solve: Simplifying -8 + -1w = 0 Solving -8 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1w = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1w = 0 + 8 -1w = 0 + 8 Combine like terms: 0 + 8 = 8 -1w = 8 Divide each side by '-1'. w = -8 Simplifying w = -8Subproblem 2
Set the factor '(3 + -1w)' equal to zero and attempt to solve: Simplifying 3 + -1w = 0 Solving 3 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1w = 0 + -3 -1w = 0 + -3 Combine like terms: 0 + -3 = -3 -1w = -3 Divide each side by '-1'. w = 3 Simplifying w = 3Solution
w = {-8, 3}
| 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 | | y=5-8x | | 12x-10=4x-5 | | 2x+3=33+7x | | (-3y^2-8y)+(6y^2+y-9)= | | 18(4/9) | | -4/7+2/5u=-1/2 | | -4+7x=x+20 | | 9x+6=3x-2 | | 5(8)+8y=40 | | x*x+6x+c= | | 6y^2+11=4y | | 10/15x=8 | | X/8=x+3/20 | | 5+2n=31 | | m^2-54=3m | | 3-3x=5x-85 | | 20/10x |